Detecting changes in the blood flow of the optic disk in patients with nonarteritic anterior ischemic optic neuropathy via optical coherence tomography–angiography - Xiao, Qing; Sun, Chuan-bin (Frontiers in Neurology, 2023)
Purpose This study aimed to evaluate the changes in the blood flow of the optic disk in patients with nonarteritic anterior ischemic optic neuropathy (NAION) using optical coherence tomography–angiography (OCTA) and to investigate the relationship among the changes in the blood flow of the optic disk, visual field defect, peripapillary retinal nerve fiber layer (RNFL), and macular ganglion cell complex (mGCC). Methods This was a prospective observational case series study. A total of 89 patients (89 eyes) with NAION were included in this study. All patients underwent best corrected visual acuity (BCVA), slit-lamp and direct ophthalmoscopic examinations, color fundus photography, visual field test, and blood flow indicators of the radial peripapillary capillaries (RPC) including whole en face image vessel density (VD), peripapillary VD by OCTA, the peripapillary RNFL, and mGCC by spectral-domain optic coherence tomography (OCT). The changes of blood flow in the optic disk at ≤3, 4–8, 9–12, 13–24, and >24 weeks of the natural course of NAION were measured, and the relationship among the changes in the blood flow of the optic disk, visual field defect, peripapillary RNFL, and mGCC was also analyzed. Results The mean age of 89 patients with NAION was 56.42 ± 6.81 years (ranging from 39 to 79). The initial RPC whole en face image VD was significantly reduced after acute NAION (≤3 weeks) (F = 45.598, P < 0.001) and stabilized from the eighth week onward. Over the course of NAION, the superonasal RPC, superior mGCC, and superotemporal RNFL decreased mostly with time (F = 95.658, 109.787, 263.872, respectively; P < 0.001). Maximal correlations were found between superior mGCC and temporosuperior RPC in the NAION phase (R = 0.683, P < 0.01) and between superonasal RPC and superonasal RNFL (R = 0.740, P < 0.01). The mean defect was correlated with temporosuperior RPC (R = −0.281, P < 0.01) and superior mGCC (R = −0.160, P = 0.012). Conclusion Over the course of NAION, OCTA shows a tendency toward change in the retinal capillary plexus of the optic disk. OCTA is proved to be a practical and useful tool for observing papillary perfusion in NAION.